Allosteric Modulators: Potential Treatment for Schizophrenia - Daya, Ritesh (The Meducator, 2012)
As an Honours Life Science student, Ritesh Daya worked in the department of Psychiatry and Behavioural Neuroscience. Following a presentation of his work at the Ontario Undergraduate NeuroXchange conference, Ritesh was given an award for best poster presentation by a group of delegates from The Meducator. Under the supervision of Dr. Ram Mishra, Ritesh has been investigating the pathophysiological mechanisms that underlie schizophrenia, a severe and debilitating mental illness. The focus of his research involves testing a novel allosteric modulator to potentially treat schizophrenia and other dopamine-related disorders.